Hybridity and the construction of a Malayan cultural tradition: Selected works in Malayan modern art - Ong, E. (2015)
This paper examines selected artworks produced by Malayan artists of Chinese descent during the 1950s and 60s within the contexts of Malayan nationalism and cultural tradition. The artists mentioned here went overseas for art education from the 1950s onwards and returned to Malaya as art teachers and/or artists. They include Yeoh Jinleng, Lee Joo For, Cheong Laitong, Patrick Ng Kah Onn, and Chuah Thean Teng. These artists were mostly educated in Western universities with the exception of Chuah Thean Teng. The latter although educated in Amoy Academy of Art in China, learnt Western painting alongside Chinese traditional painting. Cheong Laitong and Patrick Ng were mostly selftaught but later also studied at western colleges. The artworks discussed in this paper form an interesting contribution to a Malayan cultural imagining during that period. While local art historical writing frequently discuss their works as derivative of Western artistic movements and mostly detached from nationalistic discourse, I argue that the significance of their work lay in their claims for an authentic Malayan identity through the notion of hybridity. Their works may be viewed as a construction of Malayan cultural identity that was centred on the idea of the plurality of the different ethnic communities that make up the population of Malaya. Their notion of Malayan identity was built on the foundation of a Malayan nationalist sentiment and spirit that emerged during the 1950s.